A 2021 Update on Syphilis: Taking Stock from Pathogenesis to Vaccines - Giorgio Tiecco (MDPI AG, 2021)
In 2021 the scientific community’s efforts have been focused on solving the back-breaking challenge of the COVID-19 pandemic, but sexually transmitted infections (STI) are still one of the most common global health problems. Syphilis is a systemic disease caused by the spirochaete Treponema pallidum (TP) and is one of the oldest known diseases. Its incidence has increased in the last few years and syphilis still remains a contemporary plague that continues to afflict millions of people worldwide. Despite research improvements, syphilis pathogenesis is not completely clear; clinical presentation is very heterogeneous and the diagnosis can sometimes be difficult. Furthermore, few therapeutic options are available, and a vaccine has not been found yet. In this review, we describe the most recent evidence concerning the clinical manifestation, diagnosis, treatment and vaccine prospectives for this disease.